Pengalaman Nasabah Terhadap CSR Perbankan Berbasis Pemberdayaan UMKM dan Implikasinya bagi Kepuasan Pelanggan di Sulawesi Tenggara - Titien Rahayuningsih; Andi M Budihard (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the form and implementation of MSME-based banking Corporate Social Responsibility (CSR), MSME customers' experiences with the program, and its implications for customer satisfaction in Southeast Sulawesi. This study uses a qualitative approach with a case study type. Five informants were selected purposively, consisting of the bank branch manager, the person in charge of CSR or MSME empowerment, two MSME customers receiving the program, and one account officer/customer service. Data were collected through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that MSME-based banking CSR is realized through business training, financial literacy, business mentoring, production facility assistance, and product promotion facilitation. MSME customers responded positively because the program was considered to be appropriate to their needs, provided real benefits, and supported by good service. This experience contributed to customer satisfaction, which was reflected in increased trust, comfort, emotional closeness, and loyalty to continue using the bank's services and recommending it to others. This finding confirms that customer experience is an important factor linking CSR implementation with customer satisfaction, so that the sustainability of the program and the quality of bank-customer interactions need to be continuously strengthened.